Veio-me um 'click' na cabeça: The Theoretical Foundations and the Design of a Psycholinguistically Oriented, Empirical Investigation on German-Portuguese Translation Processes - Alves, Fábio (Meta, 1996)
AbstractThis article outlines the theoretical foundations and the design of a research project concerning a psycholinguistically oriented investigation of translations from German into Portuguese. Within an empirical framework it aims to analyse data collected among Portuguese and Brazilian translators using the thinking-aloud technique. Building on it, it cross-examines the issue in its linguistic and cultural aspects, throwing light on and contributing to the development of the methodology of translation teaching as a whole and, more specifically, in relation to the linguistic pair German/Portuguese.